Criminal Liabialty Based On the Child Nutrition of Vicarious Liabialty for Poisoning Cases in the Child Nutrition Program - Silvia Aprilia; Yogi Prasetyo; Ferry Irawan Febriansyah (LPPM Institut Pendidikan Nusantara Global, 2026)
The purpose of this study is to analyze criminal liability based on vicarious liability in a mass poisoning case that occurred during a nutritious food program for children, a government policy aimed at improving the nutritional quality of students. The problem arose when the food provided by the organizer did not meet food safety standards, resulting in harm to children as consumers who are legally entitled to safety and security as stipulated in the Consumer Protection Law. The approach used in this study is a normative legal method, analyzing legislation, legal doctrine, and the concept of criminal liability within the framework of employment relationships. The results of this study indicate that the program involved many parties, including local governments, catering providers, schools, and third parties involved in distribution. Therefore, the principle of vicarious liability is relevant for assessing the criminal liability of those who benefited, had authority, and were negligent in supervising the program. In conclusion, the application of the principle of vicarious liability can provide clarity regarding the primary responsibility in cases of negligence that lead to poisoning. It also serves as a basis for strengthening oversight mechanisms to ensure that the public program's goal of fulfilling children's rights does not become a potential loss to the community.